Cultural Frameworks of Consumerism: A Comparative Study of Global Brand Narratives in Bollywood and Hollywood Commercial Films - Deddy Desmal (Asian Journal of Media and Culture, 2025)
This study explores how commercial media from Bollywood and Hollywood represent and promote consumerist culture. Cultural globalization has caused the film industry, especially Bollywood and Hollywood, to become significant tools in shaping and influencing consumerist values in society. Using a qualitative approach based on literature review, this research analyzes the representation of consumerism in films from both industries and how audiences respond to consumerist portrayals within their cultural contexts. The study aims to investigate how consumerist values are promoted in these industries and their impact on societal consumption behavior. Data used includes film texts, scientific articles, journals, and books related to consumerism in mass media. The findings indicate that both Bollywood and Hollywood strongly depict consumerism through portrayals of luxurious lifestyles, branded goods, and consumption aspirations embedded in film narratives. While similarities exist in their promotion of consumerism, Bollywood emphasizes traditional and familial values, whereas Hollywood tends to prioritize individualism and luxury lifestyles. This research provides deeper insight into the role of film media in shaping global consumption and contributes to understanding globalization’s influence on consumer behavior.